Suppression of the vortex-induced vibration of a circular cylinder surrounded by eight rotating wake-control cylinders. (October 2017) - Silva-Ortega, M.; Assi, G.R.S.
Abstract: The present work investigates the use of a polar array of 8 wake-control cylinders as a means of suppressing the vortex-induced vibration (VIV) of a larger circular cylinder. The diameter of the control cylinders and their rotation speed were the main parameters investigated. Experiments have been performed in water at Reynolds numbers between 5000 and 50, 000. The rotating cylinders suppressed the peak amplitude of displacement by around 70% when compared to that of a bare cylinder. A similar response was obtained even if the rotation speed of the control cylinders was kept constant in relation to the flow speed. A specific configuration with 8 non-rotating control cylinders achieved an even better 99% suppression. As a consequence of reduced vibrations, the fluctuation of lift and mean drag were not as amplified due to VIV. The results pave the way for further studies concerning system optimization and support the development of efficient VIV suppressors and dynamic positioning systems for large floating offshore platforms and other applications.